Activities of Small-Scale Gravity Waves in the Upper Mesosphere Observed From Meteor Radar at King Sejong Station, Antarctica (62.22°S, 58.78°W) and Their Potential Sources - Song, B. G.; Song, I. S.; Chun, H. Y.; Lee, C.; Kam, H.; Kim, Y. H.; Kang, M. J.; Hindley, N. P.; Mitchell, N. J. (Journal of Geophysical Research: Atmospheres, 2021)
Gravity wave (GW) activities in the upper mesosphere (80–100 km) and their potential sources are investigated using meteor radar observations at King Sejong Station, Antarctica (KSS; 62.22°S, 58.78°W) during recent 14 years (2007–2020). GW activities are estimated by horizontal wind variances of small-scale GWs (periods <2 h, horizontal wavelength <400 km, or vertical wavelength <3–5 km). The wind variances show clear semiannual variations with maxima at solstices, and annual variations are also seen above z = 90 km. The deseasonalized wind variances at z = 96.8 km have a statistically significant periodicity of ∼11 years that can be associated with solar cycle variations. Three major potential GW sources in the lower atmosphere are examined. Orography is a potential source of GWs in winter and autumn, when the basic-state wind is westerly from the surface up to the mesosphere. The residual of the nonlinear balance equation (RNBE) at 5 hPa, a diagnostic of the GWs associated with jet stream, is the largest in winter and has a secondary maximum in spring. The correlation between the observed GWs and RNBE is significant in equinoxes, while correlation is low in winter. Deep convection in storm tracks is a potential source in autumn and winter. Secondary GWs generated in the mesosphere can also be observed in the upper mesosphere. Ray-tracing analysis for airglow images observed at KSS indicates that secondary GWs are mostly generated in winter mesosphere, which may be associated with the breaking of orographic GWs.